Simultaneous Resource Accumulation and Payoff Allocation: A Cooperative Fuzzy Game Approach - Surajit Borkotokey; Rupok Neog; Qiang Zhang (Advances in Fuzzy Systems)
We develop a simultaneous resource accumulation and payoff allocation algorithm under the framework of a cooperative fuzzy game that builds on our earlier work on the role of satisfaction in resource accumulation and payoff allocation. The difference between the two models lies in the fact that while focus was more on getting an exact solution in our previous model, the negotiation process in the current model accounts more for the role of the intermediate stages. Moreover we characterize our solution using two properties: asymptotic fairness and efficiency. Our model includes a suitable penalty function to refrain players from unreasonable demands. We focus on real life situations where possibly one or more players compromise on their shares to ensure a binding agreement with the others.